PENGARUH TERAPI RENDAM KAKI AIR HANGAT DENGAN KOMBINASI DZIKIR TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI PUSKESMAS DUNGALIYO - Fadli Syamsuddin; Andi Nuraina Sudirman (-, 2021)
The objective of this research is to find out Soak Feet on Warm Water Therapy with Combination of Dzikir on hypertension Incidence at Puskesmas Dungaliyo. Design of research used pre-eksperiment design with one group pre test-post test approach. Sampeling through accidental sampling on 30 respondentswhich used One samples T-test statistical test the result showed in one group who gived Soak Feet on Warm Water treatment and DZIKIR combination before and after then there are significance influence of Soak Feet on Warm Water with Dzikir combination in decreased hypertension in patients at puskesmas dungaliyo marked by P value 0.000 <a0,05